SETELAH JIHAD DAN BOM: DISKURSUS DAKWAH PADA MASYARAKAT PLURAL (Harmoni, 2012)
Jihad is the doctrine or the call of God towards earnest accomplishment. A number of Muslims examine  QurΓÇÖan and Hadith texts on order above law because of the unavailability of qathΓÇÖi quotations. This effort is called ijtihad and the person undergoing thr process is is called mujtahid. In Islamic communities there are also people who are trying earnestly to become pure through a series of repentance and remembrance, they are called mujahadah. At this time, the word jihad is much more popular than the word ijtihad and mujahadah. However, the fact is the words are a form of application of Islamic Teachings which has proved to change the mentality of the Muslim Nations from the act of unjust, immorality, and hostility towards each other to be the superior race (khaira umma) and contribute to humanity, justice and prosperity. In regards of the doctrine of jihad, it is often absent of the spirit of ijtihad and mujahadah, thus its impact and acknowledgement is less experienced by neither Muslims nor the whole human race. Preaching is the right choice for fulfilling the mission as khalifatullah in plural societies in the globalization era. By preaching, Muslims can make changes as required by  Islam. It is proven that dogmas and Islamic  Jihad movements with a qital approach is  left behind as compared to Islamic movement which prioritizes the preaching approach. Progress after progress has been made by the missionary movement, while the failures have been experienced by the jihadist movements. History is a wise and yet objective teacher.
Keywords: dakwah dan pluralitas; preaching and plurality; mujahadah; ijtihad; Jihad